State and perspectives of investigations in anthropomorphology of soft parts in Poznań - Kolaczkowski , Zdzisław (Anthropological Review, 1974)
The author presents historicaly the beginning and development of investigations in anthropomorphology of muscles in scientific institutions of Poznan. Finally he gives a review of the present-day state of this investigations.